PERLINDUNGAN HUKUM PEMEGANG POLIS DALAM HAL PAILITNYA PERUSAHAAN ASURANSI - wiarti, watty (JURNAL ILMIAH LIVING LAW, 2015)
This research aims to identify and analyze how the legal protection of policyholders and how to balance the legal protection of creditors, debtors and society. The author uses the method of juridical and normative research uses a qualitative approach, the findings and analysis will be prepared with descriptive approach. The results showed that the institution of bankruptcy in Indonesia in the legal protection of creditors, debtors and society, yet can accommodate a comprehensive settlement of disputes bankruptcy. This study suggests that the principles of good corporate governance is characterized by fairness and justice, transparency or openness, accountability, and responsibility, to be used as input in the relevant reform legislation relating to business law, particularly insurance and bankruptcy law.